THE IMPACT OF KOREAN WAVE CULTURE ON THE DEVELOPMENT OF GENERATION Z FROM THE PERSPECTIVE OF ISLAMIC ETHICS - Karim, Ahmad Abdul; Farihah, Irzum (Sekolah Tinggi Agama Islam Sadra, 2025)
This study analyses the influence of the Korean wave, or hallyu, on the potential erosion of local culture among Indonesia’s Gen Z, as well as how they can harmonize local values with the principles of Islamic philosophy. The Korean wave phenomenon is growing rapidly along with advances in technology and social media, which strengthens Gen Z’s interaction with foreign cultures. This phenomenon has not only affected many young generations in various countries, including Gen Z in Indonesia. This study uses a descriptive qualitative approach to examine the influence of the Korean wave on Gen Z cultural values ​​within the framework of Islamic philosophy. The data in this study were obtained through several data collection techniques, including structured interviews and direct observations conducted in various Korean wave fan communities to observe behavioral patterns, social interactions, and how the influence of Korean culture is reflected in the daily lives of Gen Z, and data analysis was conducted using an interpretative approach. This study shows the positive impacts of the Korean wave or hallyu, such as increased interest in learning foreign languages, enhanced creativity, and greater appreciation for the arts. However, there is a risk of diminishing local cultural identity. Therefore, Gen Z must balance the acceptance of foreign cultures with the preservation of local traditions through a lifestyle grounded in Islamic values. According to Ibn Miskawayh, the development of moral character and self-control is essential in filtering external cultural influences. This approach enables young people to remain open to globalization while maintaining their cultural and spiritual identity.